Fecal microbiota transplantation mitigates postdieting weight regain in mice by modulating the gut-liver axis - Hong Cao; Jiangwei Xu; Han Wang; Wanya Yi; Dandan Yang; Ju Yang; Jing Sun; Yingyu Wang; Feng Zhang; Jiai Yan; Dan Li (BMC Microbiology)
Abstract Background Dysbiosis of the microbiome is strongly associated with weight rebound after dieting. However, the interactions between the host and microbiome and their relevance to the pathogenesis of post-diet weight rebound remain unclear. Purpose This study aimed to evaluate the effects of fecal microbiota transplantation (FMT) on post-diet weight regain and to investigate the underlying mechanisms by which FMT inhibits weight regain. Methods FMT was administered once daily to mice for 5 weeks. Gas chromatography tandem mass spectrometry was employed to analyze short-chain fatty acid levels in serum, ultrahigh-performance liquid chromatography tandem mass spectrometry was utilized for analyzing hepatic lipid metabolites, and shotgun metagenomic sequencing was applied to examine the intestinal microbiome. Results FMT reduced weight regain and prevented lipid accumulation in both liver and adipose tissue while also improving glucose intolerance in mice. Furthermore, FMT increased the abundance of Enterorhabdus caecimuris and decreased the abundances of Burkholderiales, Sutterellaceae, Turicimonas muris, Bacteroides stercorirosoris, and Acetivibrio ethanolgignens within the gut microbiota. Additionally, elevated propionic acid levels and significant alterations in hepatic lipid metabolites were observed following FMT administration. Conclusions Our findings demonstrate that FMT effectively mitigates post-diet weight regain and associated complications. These effects are mediated through interactions between the gut microbiota and the liver via the gut-propionic acid-liver axis. Clinical trial number Not applicable.